Model Pemberdayaan Ekonomi Terhadap Kemandirian Masjid Haji Maraset Jl. Sei Deli Kecamatan Medan Barat - Muhammad Arif; Ali Hanafiyah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
This research examines economic empowerment in mosque independence. This study uses a qualitative research method by means of observation, namely researchers conduct observations and interviews directly with the parties concerned, especially advisors, chairpersons, and members of ta'mir Maraset Hajj mosque. The results are analyzed by stages of data reduction, data presentation and verification or make conclusions. This research was conducted to determine the extent of economic development concept of Hajj Maraset mosque, explaining the implementation of economic empowerment in managing the economic potential on Hajj Maraset mosque, and identifying mosques contribution to the welfare of the community in the Maraset Hajj mosque. An economic role that has not been maximized, researchers offer: mosque development-based culinary businesses, mosque development-based mini markets, banks, and if the mosque has more land, the mosque develops cattle, goats and chickens with cutting services in accordance with Islamic sharia. There are three reasons for the Haji Maraset mosque to be categorized as an independent mosque: it can fund activities planned by the mosque by optimizing the potential sources of funds owned by the mosque, has the ability to produce income professionally through optimizing asset empowerment, and managing professionalism in all activities and prosperity of the mosque.